2016
DOI: 10.1186/s13568-016-0176-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel oxidase from Thelonectria discophora SANK 18292 involved in nectrisine biosynthesis

Abstract: A fungus, Thelonectria discophora SANK 18292 (JCM 30947), produces nectrisine that has a nitrogen-containing heterocyclic 5-membered ring acting as a glycosidase inhibitor. Our previous study showed the possibility that 4-amino-4-deoxyarabinitol was enzymatically converted to nectrisine but the enzyme was not known. In order to characterize the enzyme, which is designated as NecC, it was purified from the fungus using ammonium sulfate precipitation and anion exchange chromatography. Liquid chromatography-tande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Since NecC is an alcohol oxidase, 4-amino-4-deoxyarabinitol is considered to be first converted to an aldehyde (compound 3) with intramolecular addition of the amino group to the carbonyl group, resulting in a cyclic compound (compound 4) that could be spontaneously dehydrated (without an enzymatic reaction) to afford nectrisine (20). Our results also indicated that necA, encoding a putative aminotransferase, is involved in 4-amino-4-deoxyarabinitol biosynthesis.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Since NecC is an alcohol oxidase, 4-amino-4-deoxyarabinitol is considered to be first converted to an aldehyde (compound 3) with intramolecular addition of the amino group to the carbonyl group, resulting in a cyclic compound (compound 4) that could be spontaneously dehydrated (without an enzymatic reaction) to afford nectrisine (20). Our results also indicated that necA, encoding a putative aminotransferase, is involved in 4-amino-4-deoxyarabinitol biosynthesis.…”
Section: Discussionmentioning
confidence: 52%
“…A cosmid library of T. discophora genomic DNA was constructed and necCpositive cells were screened as described previously (20). Briefly, the cosmid library was constructed using SuperCos1 cosmid vector (Agilent Technologies), with E. coli XL1-Blue MR as the host strain.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations